PENDIDIKAN KESENIAN DALAM PEMBANGUNAN KARAKTER BANGSA - K Kasiyan (LPMPP Universitas Negeri Yogyakarta, 2002)
The aim ofeducation in art in the context ofthe public schoolin Indonesia is paradigmatically oriented more to the perspective ofunderstanding